FROM CONVENTIONAL FERTILIZATION TO INTELLIGENT CULTIVATION: HARNESSING TRICHODERMA-BASED TRICHOCOMPOST TO SUPPORT SUSTAINABLE AGROINDUSTRY 4.0 IN MAIZE PRODUCTION - Rida Iswati; Angry Pratama Solihin; Siska Irhamnawati Pulogu; Sofyan S. Rudin (Gunung Djati Conference Series, 2026)
Maize production in low-organic-matter soils requires cultivation technologies that can sustain yield while reducing dependence on inorganic fertilizers. Trichocompost enriched with local Trichoderma isolates offers a promising biological input to improve soil function, plant growth, and productivity. This study evaluated the effectiveness of trichocompost prepared with Trichoderma asperellum TZ11DI1 and Trichoderma reesei TZ31DU1 on maize growth, biomass, and yield components under reduced inorganic fertilizer application. The field experiment was conducted in Gorontalo Province, Indonesia, using a randomized complete block design with three treatments and three replications: full recommended inorganic fertilizer without trichocompost, 75% inorganic fertilizer combined with TZ11DI1 trichocompost, and 75% inorganic fertilizer combined with TZ31DU1 trichocompost. Growth, root development, biomass, and yield components were measured during vegetative growth and after harvest. The results showed that both trichocompost treatments improved plant height, number of leaves, root length, root biomass, shoot biomass, ear development, kernel weight, and 1000-kernel weight compared with the control. TZ11DI1 produced the best performance in most shoot and yield parameters, including plant height, leaf number, shoot biomass, ear weight, kernel weight, and 1000-kernel weight, whereas TZ31DU1 was more effective in increasing root length and root biomass. These findings indicate that local Trichoderma-based trichocompost can maintain and enhance maize productivity while reducing inorganic fertilizer use by 25%. This technology provides a practical and environmentally friendly strategy for sustainable maize cultivation and supports biological innovation in Agroindustry 4.0.